PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 013 BASILAM BARU - Nova Ariati Nova Ariati; Mahmud Alpusari Mahmud Alpusari; Munjiatun ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrack. The classroom Action Research (CAR) this purpose to increase the result study sains student to passed class IV SDN. 013 Basilam Baru apllay STAD Cooperative Learning Model Type conducted in March to April. Class IV students study the subject SDN 013 Basilam Baru amounting to 14 students. Parameters of this study is the result of student learning, teacher and student activities. The results showed that the learning outcomes of students has increased in the first cycle the average being 77.85 (medium) and second cycle average of 82.85 (high), mastery learning students from the first cycle 57, 14% (not finished), the cycle II increased to 92, 85% (complete). And activities of teachers in the first cycle the first meeting of the percentage gain of 41.2% increase in the second meeting to 58, 3%. In the second cycle first increases 75% and the second peremuan be 91.7%. While aktvitas students also increased in the first cycle in which the first meeting of a 37.5% increase at the second meeting to 54.2%. And the second cycle of the first-mentioned meeting 66.7% increased to 83, 3%. From the results of this study that the type STAD Cooperative Learning Model can improve learning outcomes SAIN class IV students of SDN 013 Basilam Baru. Keywords: Model, Type STAD Cooperative Learning, Learning Outcomes SAIN